A review on the aerodrome standard in the aviation industry - Law, Mohd Syafiq Aidil; Ariffin, Ahmad Hamdan (FAZ Publishing, 2020)
The aviation industry consists of a few branches such as Flight Operation, Air Traffic Control Management, Airworthiness and Aerodrome Standards. Aerodrome standard is related to the airport operation, which following the International Civil Aviation Organisation (ICAO). The essential element in aerodrome or airport can be listed such as runway, apron, terminal, maintenance hangar and taxiway. Several issues are highlighted in the taxiway segment, which required further review, especially on the Aeronautical Ground Lighting system. Aeronautical Ground Lighting system is the most crucial part in taxiway because it gives guidance to a pilot in taxiway to avoid aircraft incursion. Therefore, this paper will give focus on the taxiway, especially on the Aeronautical Ground Lighting system, which is related to the daily operation requirements for airports.